Ethereum Blockchain-Based Weather Data Storage Prototype - Sulistiyani, Eris; Prastowo, Bambang Nurcahyo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
The application of Ethereum Blockchain within IoT-based weather monitoring systems presents substantial potential for enhancing data security, integrity, transparency, and trust. This study is focused on the design, implementation, and evaluation of Ethereum Blockchain as a robust data security mechanism in an IoT weather monitoring system. The system is configured to monitor environmental parameters, specifically temperature and humidity, using DHT22 sensors, with data securely stored and processed through smart contracts on a locally deployed Ethereum network. The research utilizes the Proof of Authority consensus mechanism, assessing data transmission and storage latency across varying mining intervals. The findings reveal minimal transmission delays, whereas storage delays on the blockchain exhibit variability, influenced by the duration of the mining period. Specifically, longer mining intervals contribute to increased delays in data storage. These results underscore the necessity of optimizing the mining interval to ensure complete and synchronized data storage, thereby enhancing the accuracy and reliability of the weather monitoring system. This study demonstrates the efficacy of Ethereum Blockchain in addressing critical challenges related to data security and integrity within IoT applications, highlighting its potential as a promising solution for secure data management.